Increased Blood Retinol Levels Are Associated With a Reduced Risk of TIA or Stroke in an Adult Population: Lifestyle Factors- and CVDs-Stratified Analysis - Linjuan Guo (Frontiers Media S.A., 2021)
Background: Data on the existing evidence for the association between blood retinol and transient ischemic attack (TIA)/stroke risk are limited, and the results are inconclusive. This study aimed to further assess the associations between the blood retinol levels and the risk of TIA/stroke after controlling the lifestyle factors and age-related confounders.Methods: The cross-sectional data from 1,113 individuals (aged 34–84 years old) were obtained from the Midlife in the United States (MIDUS) study. The multivariable analyses were performed to investigate the association of blood retinol levels with ever and currently TIA/stroke.Results: There was an inverse association between the blood retinol levels and the risk of ever TIA or stroke (for per 1 μmol/L adjusted odds ration [OR]: 0.93; 95% CI: 0.89–0.97; for per 1-SD adjusted OR: 0.89; 95% CI: 0.83–0.96) and currently diagnosed TIA or stroke (for per 1 μmol/L adjusted OR: 0.91; 95% CI: 0.87–0.96; for per 1-SD adjusted OR: 0.84; 95% CI: 0.80–0.91) after controlling the lifestyle factors and age-related confounders. The significance of these associations was maintained after a sensitivity analysis and involving “ever chronic respiratory diseases” as a covariate. Moreover, the stratified analyses suggested that the inverse associations could be affected by overweight [body mass index (BMI) ≥ 28, kg/m2], hypertension, and diabetes.Conclusions: A significant inverse association between blood retinol and the risk of TIA or stroke was found. This inverse association did not change even after adjustment for many potential confounders. Moreover, the potential protective effect of retinol on TIA/stroke could be blunted by overweight [BMI ≥ 28, kg/m2], hypertension, and diabetes.